AETA 2016: Recent Advances in Electrical Engineering and Related Sciences Theory and Application - Duy, Vo Hoang; Dao, Tran Trong; Kim, Sang Bong; Tien, Nguyen Tan; Zelinka, Ivan (Lecture Notes in Electrical Engineering, 2017)
These lecture notes present selected topics concerning a wide range of electrical and electronics applications, highlighting innovative approaches and offering state-of-the-art overviews. The book is divided into 14 topical areas, including e.g. telecommunication, power systems, robotics, control systems, renewable energy, mechanical engineering, computer science and more. Readers will find revealing papers on the design and implementation of control algorithms for automobiles and electrohydraulic systems, efficient protocols for vehicular ad hoc networks and motor control, and energy-saving methods that can be applied in various fields of electrical engineering. The book offers a valuable resource for all practitioners who want to apply the topics discussed to solve real-world problems in their challenging applications. Offering insights into common and related subjects in the research fields of modern electrical, electronic and related technologies, it will also benefit all scientists and engineers working in the above-mentioned fields. .